The effects of exercise frequency on executive function in individuals with Parkinson's disease. (March 2016) - Caciula, Manuela C.; Horvat, Michael; Tomporowski, Phillip D.; Nocera, Joe
Abstract: Introduction: Cognitive function impairments can be observed early in Parkinson's disease (PD). Although exercise is considered a valuable tool in delaying the progression of disease related outcomes, the optimal frequency of exercise interventions has not been identified. Our purpose was to identify the effects of different frequencies of chronic exercise training on aspects of executive function, specifically cognitive flexibility and working memory in PD. Methods: Forty-three participants (M age = 68.5 (SD = 11.3), 26 males), with idiopathic PD completed a category switching task and an N-back task at baseline and after 12 weeks of multimodal exercise training. The participants were divided into two training frequency groups: high-frequency: 4–5 times each week (N = 23, M age = 68.6 (SD = 5.8), 16 males), and low-frequency: 3 times or less each week (N = 20, M age = 67.6 (SD = 4.5), 10 males). Results: Both frequency groups improved in executive function, showing improved global switch-cost accuracy (F (1, 41) = 5.08, p<.05, η_pˆ2 = 0.11) and N-back accuracy (F (1, 41) = 17.37, p < 0.001, η_pˆ2 = 0.29). The highfrequency group displayed significantly greater reductions in global switch costs (F(1, 41) = 5.53, p < 0.05., η_pˆ2 = 0.09), and working memory response time (F(1, 41) = 14.96, p<0.001, η_pˆ2 = 0.26), than the low-frequency group. Conclusions: A high frequency, multimodal exercise program involving aerobic, strength, and flexibility exercises has a better impact on executive functioning in PD than a low-frequency exercise intervention. Highlights: Exercise is considered a valuable tool in delaying the progression of Parkinson's disease related outcomes. The optimal frequency of exercise interventions has not been identified. We propose a high-frequency and a low-frequency multimodal exercise intervention for 12 weeks. We report that high-frequency exercise may preserve executive functioning in PD.